2002
DOI: 10.1007/s00213-002-1194-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute trytophan depletion decreases intensity dependence of auditory evoked magnetic N1/P2 dipole source activity

Abstract: ATD decreased the intensity dependence of N1m/P2m source dipole moments in the primary auditory cortex at the hemisphere contralateral to the ear stimulated. These results suggest that serotonin participates in the regulation of intensity of auditory stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 40 publications
6
39
0
Order By: Relevance
“…However, despite such pronounced levels of tryptophan depletion in the current study, no significant effect was noted on the LDAEP. This result is consistent with the majority of previous studies using ATD which similarly found no effects on the LDAEP (Debener et al, 2002;Dierks et al, 1999;Massey et al, 2004), although a paradoxical decrease in the LDAEP has been noted following ATD in one study (Kähkönen et al, 2002). These variable results using ATD methodology are analogous to other investigations reporting inconsistent outcomes following acute serotonin augmentation using SSRIs.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, despite such pronounced levels of tryptophan depletion in the current study, no significant effect was noted on the LDAEP. This result is consistent with the majority of previous studies using ATD which similarly found no effects on the LDAEP (Debener et al, 2002;Dierks et al, 1999;Massey et al, 2004), although a paradoxical decrease in the LDAEP has been noted following ATD in one study (Kähkönen et al, 2002). These variable results using ATD methodology are analogous to other investigations reporting inconsistent outcomes following acute serotonin augmentation using SSRIs.…”
Section: Discussionsupporting
confidence: 92%
“…This ratio of amino acid precursor to LNAA is thought to be a more accurate reflection of the amount of central depletion of the precursor (Fernstrom, 1979;Van der Does, 2001). This level of depletion is comparable to, if not exceeding that obtained in other studies involving the LDAEP (Debener et al, 2002;Dierks et al, 1999 andKähkönen et al, 2002). In addition, these levels of depletion have been shown to significantly affect measures of central serotonergic function such as brain serotonin synthesis (Moja et al, 1988;Nishizawa et al, 1997) and CSF concentrations of serotonin metabolites (Carpenter et al, 1998;Williams et al, 1999).…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations